Thomas Hauser on sports : remembering the journey - Hauser, Thomas (The University of Arkansas Press, 2013)
Thomas Hauser is best known to sports fans as Muhammad Ali's biographer and for his recording of the contemporary boxing scene. Booklist says that Hauser is "the most respected boxing journalist working today and perhaps the best ever." Robert Lipsyte calls him "the best boxing writer of our time." This book, however, brings together Hauser's articles on sports other than boxing. The journey begins in the days of Hauser's youth and follows the games we play into the era of steroids and multi-billion-dollar television contracts. It combines personal memories with issue-oriented commentary - and offers an intimate look at some of the most remarkable athletes of the twentieth century.